2012
DOI: 10.1371/journal.pone.0050151
|View full text |Cite
|
Sign up to set email alerts
|

Flow Sorting and Molecular Cytogenetic Identification of Individual Chromosomes of Dasypyrum villosum L. (H. villosa) by a Single DNA Probe

Abstract: Dasypyrum villosum (L.) Candargy (sin. Haynaldia villosa) is an annual wild diploid grass species (2n = 2x = 14; genome VV) belonging to the Poaceae family, which is considered to be an important source of biotic and abiotic stress resistance genes for wheat breeding. Enhanced characterization of D. villosum chromosomes can facilitate exploitation of its gene pool and its use in wheat breeding programs. Here we present the cytogenetic identification of D. villosum chromosomes on slide by fluorescent in situ hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 63 publications
1
17
1
1
Order By: Relevance
“…2 e). The chromosomal distribution of (GAA) n repeats in D. breviaristatum chromosome 2V b identified herein is different from the previously known hybridization pattern of D. villosum chromosome 2V [Grosso et al, 2012].…”
Section: Chromosomal Characterizationcontrasting
confidence: 99%
See 1 more Smart Citation
“…2 e). The chromosomal distribution of (GAA) n repeats in D. breviaristatum chromosome 2V b identified herein is different from the previously known hybridization pattern of D. villosum chromosome 2V [Grosso et al, 2012].…”
Section: Chromosomal Characterizationcontrasting
confidence: 99%
“…2 ). Meanwhile, the simple sequence repeat (GAA) n can be used as a FISH probe to characterize the individual D. villosum chromosomes [Grosso et al, 2012]. In the present study, we also showed the D. villosum chromosome 2V in the addition line having strong centromeric (GAA) n signals ( fig.…”
Section: Discussionsupporting
confidence: 68%
“…Flow cytometric data were collected and analyzed using the software package CellQuest Pro v4.01 (BD Bioscience, San Jose, CA). As already described [9], the primary analysis gate was set on a dual parameter dot plot comprising Forward Scatter (FSC) versus FL1H (H =  signal height, DAPI fluorescence) to discriminate chromosomes from debris and chromosome aggregates. Sorting windows ( Figure 2 ) were drawn on the fluorescence dot plot of FL1A (A =  signal area; DAPI fluorescence) versus FL3H (FITC fluorescence) or FL4H (Cy3 fluorescence).…”
Section: Methodsmentioning
confidence: 99%
“…As of now, methods for chromosome isolation and flow sorting have been reported for 22 plant species including major cereal crops and wild relatives [7], [8], [9]. The separation of a genome into its chromosomal components offers an effective means to generate a full genome sequence of large-genome species, often polyploids such as bread wheat, since it greatly simplifies the process of sequence assembly [8].…”
Section: Introductionmentioning
confidence: 99%
“…The flowcytometric analysis of mitotic chromosomes has been reported in 24 plant species (Doležel et al 2014), including hexaploid and tetraploid wheat and their wild relatives in the genus Aegilops and Dasypyrum (Molnár et al 2011b;Grosso et al 2012). To date, flow cytometric chromosome analysis and sorting has not been reported for the diploid progenitors of bread wheat.…”
Section: Introductionmentioning
confidence: 99%